A Secret Police: The Lasting Impact of the 1986 FOIA Amendments. Issue 4 (2nd October 2018) - Jay Wagner, A.
Abstract : The 1986 Freedom of Information Act amendments were passed as a last-minute rider to Reagan-era War on Drugs legislation. The three pieces – a broad restructuring of Exemption 7, the law enforcement exemption; the addition of exclusions for law enforcement and intelligence requests; and introduction of a new fee structure – have had a lasting impact on FOIA implementation and contribute to the contemporary inability to affect police transparency. Review of the 1986 FOIA amendments' legislative history documents the White House's determination to loosen law enforcement oversight and congressional appeals to exaggerated fears of illicit drug users. The study considers the effect on judicial interpretation of Exemption 7, exploring decisions before and after the amendments, while also analyzing FOIA use and implementation patterns through a dataset of annual reports from 1975 until present. The analysis reveals a sharp increase in Exemption 7 claims and "no records" responses, both attributable to the 1986 FOIA amendments.